SERAT SULUK PAWESTRI SAMARIYAH: SEBUAH PENCARIAN TIRTAMARTA DALAM NUANSA KEJAWEN-KRISTIANI - Prabowo, Danu Priyo (Diksi, 2006)
Manuscripts of Javanese literary texts with a Christian nuance are difficultto obtain. Compared with the development of the Hindu, Buddhism, and Moslemtraditions in Javanese literary culture, that of the Christian tradition is stillrelatively new. Only a few Javanese literary texts with a Christian nuance areassumed to be currently in existence.The writer has in hand a manuscript containing a Javanese literary texttitled Serat Suluk Pawestri Samariyah. Written in the style of tembang macapat, itis to be sung aloud and, according to the year to be guessed from the four-wordedJavanese phrase called a sengkalan there, it was written in 1853 in the Javanesecalendar or in 1921 A.D. and got into print as a book published in 1925 by A. C. Nix& Co., Bandung, telling about "toya gesang utawi tirtamarta sarta bab sajatiningpanembah", or about the life-giving water or tirtamarta and about the essence ofprayers.According to a research on the literature, Serat Suluk Pawestri Samariyahhas never been scientifically studied. So this article attempts to show somethingnew to discover in the Javanese literary tradition by disclosing an acculturation to aChristian nuance in the manuscript in the essence of its content. The word sulukitself, according to the Javanese literary tradition, is at times used to call writingscontaining a mystical mixture of Islamic teachings called Tasawuf and Javaneseteachings called Kejawen. It is opined, however, that in the title of the manuscript itis intended to refer to the Christian nuance in the Javanese context of the text.Keywords: Javanese literary tradition, Christian nuanceA.